Kemampuan Representasi Siswa SMP pada Materi Pesawat Sederhana - Ayu Nurindah Sari; Oka Elvina; Arifian Dimas (Universitas Sebelas Maret, 2019)
Abstract: This study aims to determine the ability of student representation on Simple Airplane material. The research method used is descriptive qualitative. The population in this study was grade VIII students of MTS Al-Hidayah Kendal Ngawi in the academic year 2019/2020. Sampling uses purposive random sampling. The sample used was class VIII A, with a total of 26 students. The test instruments used in this study were tests and interviews. The test is in the form of multiple-choice reasoning which amounts to 10 simple aircraft material questions. Interviews conducted after researchers got test results from students. The representations examined in this study were image representations and verbal representations. The results showed that the ability of students' representation was still low. The evidenced by the results of student tests where most of the achievements are still below 50%. Lack of student ability in terms of multi-representation because students not accustomed to using representation in understanding concepts.Abstrak: Penelitian ini bertujuan untuk mengetahui kemampuan representasi siswa pada materi Pesawat Sederhana. Metode penelitian yang digunakan adalah deskriptif kualitatif. Populasi pada penelitian ini siswa kelas VIII MTS Al-hidayah Kendal Ngawi tahun akademik 2019/2020. Pengambilan Sample menggunakan purposive random sampling. Sample yang digunakan adalah kelas VIII A dengan jumlah 26 siswa. Instrumen tes yang digunakan dalam penelitian ini adalah tes dan wawancara. Tes berupa pilihan ganda beralasan yang berjumlah 10 soal materi pesawat sederhana. Wawancara dilakukan setelah peneliti mendapatkan hasil tes dari siswa. Representasi yang dikaji dalam penelitian ini adalah representasi gambar dan representasi verbal. Hasil penelitian menujukkan bahwa kemampuan multirepresentasi siswa masih rendah. Hal ini dibuktikan dengan hasil tes siswa yang sebagian besar ketercapaian masih dibawah 50%. Kurangnya kemampuan siswa dalam hal multirepresentasi dikarenakan siswa belum terbiasa menggunakan representasi dalam memahami konsep.